Effect Of Job Satisfaction And Gratitude On Organizational Citizenship Behavior - Fauziyyah, Afifah; Luzvinda, Liany (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2017)
This research aimed to examine the effect of job satisfaction (the nature of work, promotions, awards, salary, supervision, operational procedures, benefits, co-workers, and communications) and gratitude towards organizational citizenship behavior. Samples in this study as many as 200 employees of Gojumong Restaurant. The approach taken is a quantitative approach, using multiple regression analysis. The results of this study indicate that there is significant influence of variables job satisfaction and gratitude to theorganizational citizenship behavior. Minor hypothesis test results showed that artifacts arethree variables that significantly affect organizational citizenship behavior, namely coworkersand the communication of job satisfaction variables and gratitude. The implications of this research can provide input to the company to add a program tostrengthen the relationships between employees, such as recreation, habituationcommunication on superiors to subordinates and vice versa, and so the reminder to alwaysremind the gratitude like, words or pictures that can grow gratitude on each employeeposted in the locker.Â DOI: 10.15408/tazkiya.v22i1.8145